Organised crime, financial crime and criminal justice : theoretical concepts and challenges - Johnston, Ed; Jasinski, Dan; Phillips, Amber (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Organised crime and financial crime are pressing global problems, increasingly recognized as policy priorities both by national governments and international bodies and corporations. This proudly interdisciplinary collection is built on the premise that these topics are too often artificially separated, both in scholarship and the classroom. Bringing together scholars from law, the social sciences, and the humanities, this book showcases a diverse range of perspectives on these complex and compelling global issues, and the criminal justice challenges that they pose. The themes discussed include: Legal Theory and Procedure; Regulation and Enforcement; Prevention and Punishment; Media Representation and Perception. Readers are encouraged to think outside of traditional disciplinary bounds, and form their own connections and conclusions inspired by the juxtaposition of perspectives rarely seen together in the same volume"--
Introduction / Ed Johnston, Dan Jasinski and Amber Phillips -- Italy's other 'other mafia' : remediation and representations of the 'ndrangheta / Amber Phillips -- Italy's 'circle of legality' : the confiscation and social use of assets in the fight against the mafia / Stefania di Buccio and Amber Phillips -- Unexplained wealth orders and the right not to self-incriminate / Marnia Lovejoy -- The introduction of anti-money laundering legislation in the Vatican City State / Susan Clarke Garnett -- How and to what extent has public-private financial information sharing improved the UK's counter terrorist financing reporting regime? / Charlie Robson and Nicholas Ryder -- The future of criminal finance : 'bin Ladens' and the cashless society / Rikard Jalkebro and William Vlcek -- Crypto-assets and criminality : a critical review focusing on money laundering and terrorism financing / Ilias Kapsis -- Setting the conditions of competition : repositioning the neoliberal state in the fraud debate and Kate Tudor -- Representing white collar crime in the Caribbean / Lucy Evans -- Deferred prosecution agreements : a soft touch? / Oliver Charles and Umut Turksen -- The United Kingdom, organised crime and money laundering : a critical reflection / Nicholas Ryder, Samantha Bourton and Demelza Hall.
Keywords: Commercial crimes -- Law and legislation; White collar crimes -- Law and legislation; Organized crime -- Law and legislation; Financial institutions -- Law and legislation -- Criminal provisions; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Government & Business; LAW / General